A single crystal nickel-based high temperature alloy and its element composition design method

Through the study of polycrystalline nickel-based high-temperature alloys, and using technical means such as solid solution treatment and aging treatment, the relevant physical and chemical properties and properties of single-crystalline nickel-based high-temperature alloys are mapped to the complex and cost-effective design of single-crystalline nickel-based high-temperature alloys, and rapid design and efficient research and development are achieved.

CN116334450BActive Publication Date: 2025-04-04SICHUAN HANGDA NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211577803.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-06
Publication Date
2025-04-04
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

The preparation process of single-crystal nickel-based high-temperature alloys is complex and takes a long time, which leads to the problems of high time costs and waste of resources when designing new single-crystal high-temperature alloys.

Method used

By melting and casting the alloy raw materials according to the nickel-based high-temperature alloy element ratio, a polycrystalline nickel-based high-temperature alloy casting billet was obtained, and solid solution treatment and aging treatment were carried out. The γ' volume fraction and performance detection results were detected and calculated, and the element components of the single-crystal nickel-based high-temperature alloy were determined.

Benefits of technology

This method can quickly obtain elemental components of single crystal nickel-based high-temperature alloys, saving design time and cost, shortening R&D cycle, and reducing economic costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334450B_ABST
    Figure CN116334450B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of nickel-based high-temperature alloys, and specifically relates to a single-crystal nickel-based high-temperature alloy and a method for designing its elemental composition. The method for designing the elemental composition of a single-crystal nickel-based high-temperature alloy provided by the present invention comprises the following steps: melting and casting the alloy raw material according to the nickel-based high-temperature alloy element ratio to obtain a polycrystalline nickel-based high-temperature alloy ingot with different elemental composition contents; subjecting the polycrystalline nickel-based high-temperature alloy ingot to solution treatment and aging treatment in sequence, and detecting and calculating the γ' volume fraction in the polycrystalline nickel-based high-temperature alloy after aging treatment; subjecting the polycrystalline nickel-based high-temperature alloy after aging treatment to a performance test; determining the elemental composition of the single-crystal nickel-based high-temperature alloy according to the elemental composition in the polycrystalline nickel-based high-temperature alloy ingot, the γ' volume fraction in the polycrystalline nickel-based high-temperature alloy after aging treatment, and the performance test results. The method provided by the present invention greatly saves the time cost and economic cost of designing a new single-crystal nickel-based high-temperature alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nickel-based high-temperature alloys, and in particular relates to a single crystal nickel-based high-temperature alloy and an element composition design method thereof. Background Art

[0002] Nickel-based superalloys are widely used in high-temperature components in modern aircraft engines, such as high-pressure turbine blades, turbine disks, etc. With the continuous development of modern aviation technology, higher requirements are placed on the temperature resistance of superalloys. Researchers have found that the temperature resistance of single-crystal nickel-based superalloys is higher than that of cast polycrystalline nickel-based superalloys; therefore, single-crystal nickel-based superalloys have gradually attracted people's attention.

[0003] However, compared with cast polycrystalline, the single crystal preparation process is more complicated and time-consuming. In the process of developing new single crystal high-temperature alloys, it not only takes a high time cost, but also easily leads to waste of resources due to material scrapping due to composition design problems. Therefore, a simple method to guide the design of single crystal high-temperature alloys is urgently needed. Summary of the invention

[0004] In view of this, the present invention provides a design method for a single crystal nickel-based high-temperature alloy and its elemental components; the design method provided by the present invention can quickly obtain the elemental components of a single crystal nickel-based high-temperature alloy, greatly saving the cost and huge time cost of designing a new single crystal nickel-based high-temperature alloy.

[0005] In order to solve the above technical problems, the present invention provides a method for designing the element composition of a single crystal nickel-based high-temperature alloy, comprising the following steps:

[0006] The alloy raw materials are melted and cast according to the ratio of nickel-based high-temperature alloy elements to obtain polycrystalline nickel-based high-temperature alloy ingots with different element component contents;

[0007] The polycrystalline nickel-based high-temperature alloy ingot is subjected to solution treatment and aging treatment in sequence, and the volume fraction of γ' in the polycrystalline nickel-based high-temperature alloy after aging treatment is obtained by detection and calculation;

[0008] Performing a performance test on the polycrystalline nickel-based high-temperature alloy after aging treatment; the performance test includes a salt-coated hot corrosion test or an anti-oxidation test;

[0009] The element composition of the single crystal nickel-based superalloy is determined according to the element composition in the polycrystalline nickel-based superalloy ingot, the volume fraction of γ' in the polycrystalline nickel-based superalloy after aging treatment and the performance test results.

[0010] Preferably, the temperature of the solution treatment is 1250-1350° C., and the holding time of the solution treatment is 2-12 hours.

[0011] Preferably, the temperature of the aging treatment is 1000-1200° C., and the holding time of the aging treatment is 4.5-5.5 h.

[0012] Preferably, the calculation is performed using Image-ProPlus.

[0013] Preferably, the conditions of the salt-coated hot corrosion test include: a temperature of 850 to 950° C. and a time of 50 to 200 h.

[0014] Preferably, the corrosion solution for the salt-coated hot corrosion test includes sodium sulfate solution and / or sodium chloride solution.

[0015] Preferably, the polycrystalline nickel-based high-temperature alloy ingot comprises the following elements in percentage by mass:

[0016]

[0017] Preferably, the smelting temperature is 1400-1600°C.

[0018] The present invention also provides a single crystal nickel-based high temperature alloy, comprising the following components in percentage by mass:

[0019]

[0020] Preferably, the following components are included in percentage by weight:

[0021]

[0022] The present invention provides a method for designing the element composition of a single crystal nickel-based superalloy, comprising the following steps: melting and casting the alloy raw material according to the nickel-based superalloy element ratio to obtain a polycrystalline nickel-based superalloy ingot with different element composition contents; performing a solid solution treatment and an aging treatment on the polycrystalline nickel-based superalloy ingot in sequence, detecting and calculating the γ' volume fraction in the polycrystalline nickel-based superalloy after the aging treatment; performing a performance test on the polycrystalline nickel-based superalloy after the aging treatment; the performance test includes a salt-coated hot corrosion test or an anti-oxidation test; determining the element composition of the single crystal nickel-based superalloy according to the element composition in the polycrystalline nickel-based superalloy ingot, the γ' volume fraction in the polycrystalline nickel-based superalloy after the aging treatment, and the performance test results. The present invention maps the relevant physical and chemical properties and performance controlled by the element composition of the alloy itself from polycrystalline to single crystal through the study of polycrystalline alloys, provides a basis for designing the element composition of single crystal alloys, greatly shortens the research and development cycle of single crystal nickel-based superalloys, and greatly saves the time cost and economic cost of designing new single crystal nickel-based superalloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1It is the microstructure diagram of polycrystalline cast metallographic structure with different element composition;

[0024] Figure 2 The metallographic microstructure diagram of polycrystalline alloys with different element compositions after solution treatment;

[0025] Figure 3 This is the microstructure morphology of polycrystalline alloys with different element compositions after aging treatment;

[0026] Figure 4 This is the SEM image of the polycrystalline alloy after hot corrosion of sample ① coated with salt;

[0027] Figure 5 Element distribution diagram of the alloy cross section of sample ① after salt hot corrosion in Example 1;

[0028] Figure 6 This is the hot corrosion kinetics curve of polycrystalline nickel-based high-temperature alloy. DETAILED DESCRIPTION

[0029] The present invention provides a method for designing the element composition of a single crystal nickel-based high-temperature alloy, comprising the following steps:

[0030] The alloy raw materials are melted and cast according to the ratio of nickel-based high-temperature alloy elements to obtain polycrystalline nickel-based high-temperature alloy ingots with different element component contents;

[0031] The polycrystalline nickel-based high-temperature alloy ingot is subjected to solution treatment and aging treatment in sequence, and the volume fraction of γ' in the polycrystalline nickel-based high-temperature alloy after aging treatment is obtained by detection and calculation;

[0032] Performing a performance test on the polycrystalline nickel-based high-temperature alloy after aging treatment; the performance test includes a salt-coated hot corrosion test or an anti-oxidation test;

[0033] The element composition of the single crystal nickel-based superalloy is determined according to the element composition in the polycrystalline nickel-based superalloy ingot, the volume fraction of γ' in the polycrystalline nickel-based superalloy after aging treatment and the performance test results.

[0034] The present invention melts and casts the alloy raw materials according to the nickel-based high-temperature alloy element ratio to obtain a polycrystalline nickel-based high-temperature alloy ingot with different element component contents. In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably contains 2.0-9.0wt.% Al, more preferably 6-8.6wt.%, in terms of mass percentage.

[0035] In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably includes 0-11.0 wt.% Co, more preferably 5-8 wt.%, in terms of mass percentage.

[0036] In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably includes 2.0-18.0 wt. % Cr, more preferably 6-8 wt. %, in terms of mass percentage.

[0037] In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably contains 2.0-13.0 wt. % W, more preferably 4.5-11 wt. %, in terms of mass percentage.

[0038] In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably includes 0-5.0 wt. % Mo, more preferably 0-2 wt. %, in terms of mass percentage.

[0039] In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably includes 0-8.0 wt. % Ta, more preferably 4-6 wt. %, in terms of mass percentage.

[0040] In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably includes 0-8.0 wt. % Ti, more preferably 0-1 wt. %, in terms of mass percentage.

[0041] In the present invention, the polycrystalline nickel-based high-temperature alloy ingot preferably includes 60.0-80.0 wt. % Ni, more preferably 70-76 wt. %, in terms of mass percentage.

[0042] The present invention has no special requirements on the source of the nickel-based high-temperature alloy raw material, and conventional commercial products in the field can be used.

[0043] In the present invention, the smelting temperature is preferably 1400-1600° C., more preferably 1450-1580° C., and even more preferably 1480-1560° C. The present invention has no special limitation on the casting, and conventional methods in the art can be used.

[0044] In the present invention, the alloy structure of the polycrystalline nickel-based high-temperature alloy ingot is a dendrite structure.

[0045] After obtaining the polycrystalline nickel-based high-temperature alloy ingot, the present invention sequentially performs solution treatment and aging treatment on the polycrystalline nickel-based high-temperature alloy ingot, and detects and calculates the γ' volume fraction in the polycrystalline nickel-based high-temperature alloy after aging treatment. In the present invention, the temperature of the solution treatment is preferably 1250-1350°C, more preferably 1280-1340°C; the holding time of the solution treatment is preferably 2-12h, more preferably 5-10h. The present invention can reduce the dendrite segregation in the polycrystalline nickel-based high-temperature alloy ingot through solution treatment, which is beneficial to the subsequent study of polycrystalline phase structure.

[0046] In the present invention, the calculation is preferably performed using Image-ProPlus.

[0047] In the present invention, the temperature of the aging treatment is preferably 1000-1200° C., more preferably 1050-1100° C.; the holding time of the aging treatment is preferably 4.5-5.5 h, more preferably 5 h.

[0048] After aging treatment, the present invention performs performance testing on the polycrystalline nickel-based high-temperature alloy after aging treatment; the performance testing test includes a salt-coated hot corrosion test or an anti-oxidation test. In the present invention, the salt-coated hot corrosion is to dry after coating the surface of the polycrystalline nickel-based high-temperature alloy after aging treatment with a corrosive liquid. In the present invention, the corrosive liquid preferably includes a sodium sulfate solution and / or a sodium chloride solution, and more preferably a mixed solution of sodium sulfate and sodium chloride. In the present invention, the mass concentration of the corrosive liquid is preferably 90-110 g / L, and more preferably 100 g / L. In the present invention, when the corrosive liquid is a mixed solution of sodium sulfate and sodium chloride, the mass ratio of sodium sulfate to sodium chloride in the mixed solution is preferably 75-95:5-25, and more preferably 95:5 or 75:25. In the present invention, the drying temperature is preferably 0-140°C, and more preferably 80-120°C. The present invention has no special requirements for the drying time, as long as the corrosive liquid can be deposited on the surface of the polycrystalline nickel-based high-temperature alloy after aging treatment. In the present invention, the salt coating cycle of the hot corrosion test is 20 hours, that is, after being kept at the test temperature for 20 hours, the salt coating step is repeated; the number of repetitions is preferably 2 to 5 times, more preferably 4 to 5 times. In the present invention, the amount of deposition on the alloy surface is preferably 25 to 35 g / m 2 , more preferably 30g / m 2 .

[0049] In the present invention, the conditions of the salt-coated hot corrosion test preferably include: the temperature is preferably 850-950° C., more preferably 900° C.; the time is preferably 50-200 h, more preferably 60-100 h.

[0050] In the present invention, the grain orientation of the polycrystalline alloy is disordered after aging treatment. After salt-coated hot corrosion, the shape of the γ' phase in the

[001] oriented grains is square, the shape of the γ' phase in the

[110] oriented grains is rectangular, and the shape of the γ' phase in the

[111] oriented grains is triangular. Therefore, after the two-phase structure is adjusted by aging treatment, the crystal orientation in the polycrystalline alloy can be judged according to the shape of the γ' phase in the alloy grains after corrosion.

[0051] After salt hot corrosion, the present invention determines the elemental composition of the single-crystal nickel-based high-temperature alloy according to the elemental composition in the polycrystalline nickel-based high-temperature alloy ingot, the γ' volume fraction in the polycrystalline nickel-based high-temperature alloy after aging treatment, and the salt hot corrosion results. The present invention maps the hot corrosion resistance of the polycrystalline alloy to the single-crystal alloy, and designs the elemental composition of the single-crystal nickel-based high-temperature alloy with good hot corrosion resistance according to the influence of the elemental composition in the polycrystalline nickel-based high-temperature alloy ingot on the hot corrosion resistance of the polycrystalline alloy.

[0052] The present invention maps the influence of elemental components on the thermal corrosion resistance of polycrystalline alloys to the influence of elemental components in single crystal alloys on the thermal corrosion resistance. By exploring the performance of polycrystalline alloys and designing the elemental composition of single crystal alloys, the research and development cycle of single crystal nickel-based high-temperature alloys is greatly shortened and the cost of researching single crystals is reduced.

[0053] The present invention also provides a single crystal nickel-based high temperature alloy, comprising the following components in percentage by mass:

[0054]

[0055] In terms of mass percentage, the single crystal nickel-based high temperature alloy provided by the present invention comprises 6-6.5 wt. % Al, preferably 8.4 wt. %.

[0056] Calculated in terms of mass percentage, the single crystal nickel-based high temperature alloy provided by the present invention comprises 6-7.5wt.% Co, preferably 6wt.%.

[0057] Calculated in terms of mass percentage, the single crystal nickel-based high temperature alloy provided by the present invention comprises 6.5-8 wt.% Cr, preferably 8 wt.%.

[0058] In terms of mass percentage, the single crystal nickel-based high temperature alloy provided by the present invention comprises 4.5-6.5 wt. % W, preferably 6.5 wt. %.

[0059] Calculated in terms of mass percentage, the single crystal nickel-based high temperature alloy provided by the present invention comprises 0 to 2 wt.% Mo, preferably 1.5 to 2 wt.%.

[0060] Calculated in percentage by mass, the single crystal nickel-based high temperature alloy provided by the present invention comprises 0-6wt.% Ta, preferably 6wt.%.

[0061] Measured in percentage by mass, the single crystal nickel-based high-temperature alloy provided by the present invention includes a balance of Ni.

[0062] The single crystal nickel-based high temperature alloy provided by the invention has high thermal corrosion resistance.

[0063] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0064] Example 1

[0065] According to the elemental composition in Table 1, aluminum source, chromium source, tungsten source, nickel source and cobalt source are melted and cast to obtain polycrystalline nickel-based high-temperature alloy ingots, which are respectively denoted as ①, ②, ③ and ④;

[0066] The polycrystalline nickel-based high-temperature alloy ingot was solution treated at 1280-1340°C for 2-11 hours; then aged at 1100°C for 5 hours, and the γ' volume fraction of the aged alloy was calculated using Image-ProPlus, and the results are listed in Table 2;

[0067] The alloy after aging treatment was subjected to salt hot corrosion test for 100 h.

[0068] Table 1 Mass percentage of elements in polycrystalline nickel-based high-temperature alloy ingots

[0069]

[0070] Table 2 Volume fraction of γ' in alloy after aging treatment

[0071] serial number γ' volume fraction ① 77.8% ② 75.3% ③ 78.2% ④ 71.3%

[0072] According to Table 2, it can be seen that increasing the Al content, appropriately increasing the W content, and reducing the Co content are beneficial to increasing the γ' volume fraction in the alloy.

[0073] The metallographic microscope is used to detect the polycrystalline nickel-based high-temperature alloy ingot and obtain the as-cast metallographic microstructure diagram, such as Figure 1 shown by Figure 1 It can be seen that the alloy elements of the polycrystalline nickel-based high-temperature alloy ingot are unevenly distributed due to solute redistribution during the solidification process.

[0074] The metallographic structure of the alloy after solution treatment is detected by metallographic microscope, and the metallographic microstructure diagram of the alloy after solution treatment is obtained, such as Figure 2 shown by Figure 2 It can be seen that the solution treatment reduces the dendritic segregation in the alloy structure.

[0075] The microstructure of the alloy after aging treatment was detected by scanning electron microscopy, and the microstructure of the alloy after aging treatment was obtained, such as Figure 3 shown by Figure 3It can be seen that the cubic degree of the γ' phase in each alloy structure is good. The shape of γ' can be used to determine the grain orientation of the photographed area. The grains in the areas of pictures ①, ② and ③ of the alloy are close to the

[001] orientation, while the grains in the area of ​​picture ④ of the alloy are obliquely oriented to

[001] .

[0076] A mixed solution of sodium sulfate and sodium chloride (sodium sulfate mass concentration of 95%, sodium chloride mass concentration of 5%) with a total mass concentration of sodium sulfate and sodium chloride of 100 g / L was applied to the surface of sample ① after aging treatment, dried at 90°C for 0.5 h and then allowed to stand for 20 h. The deposition amount of sodium sulfate on the surface of sample ① was 28.5 g / m 2 , the deposition amount of sodium chloride is 1.5g / m 2 Repeat the coating and drying steps 5 times and then use scanning electron microscope to detect the alloy after salt coating and hot corrosion, and obtain the SEM image of the cross section of the alloy after salt coating and hot corrosion, as shown in FIG. Figure 4 The element distribution of the alloy cross section of sample ① after salt hot corrosion was detected by energy spectrometer, and the alloy element distribution diagram was obtained, as shown in Figure 5 As shown. Combined Figure 4 and Figure 5 It can be seen that there is no element segregation at the grain boundaries of the alloy cross section, indicating that the hot corrosion behavior of polycrystalline high-temperature alloys can be mapped to single-crystalline high-temperature alloys to a certain extent.

[0077] According to the sample mass weighed during the salt coating hot corrosion test, the oxidation weight gain of alloys ①②③④ during the hot corrosion process was calculated, and the hot corrosion kinetic curve of polycrystalline alloy was obtained, such as Figure 6 As shown. Figure 6 It can be seen that increasing the Al content, reducing the W content and increasing the Co content are beneficial to improving the hot corrosion resistance of the alloy.

[0078] According to Table 1, Table 2 and Figure 6 The results were comprehensively considered to determine the elemental composition of the single crystal nickel-based high-temperature alloy as Al 8.4wt.%, Cr 8.0wt.%, Co 6.0wt.%, W 6.5wt.%, and Ni 71.1wt.%.

[0079] The raw materials are subjected to vacuum induction melting according to the elemental composition and then a cast single crystal alloy test rod is prepared by a rapid solidification method.

[0080] The as-cast single crystal alloy test rod was detected to have a dendrite pattern using a metallographic microscope; the as-cast single crystal alloy test rod was subjected to gradient solution treatment as follows: 1100°C for 1h, 1200°C for 1h, 1300°C for 1h, 1310°C for 1h, 1320°C for 1h, 1330°C for 1h, and 1340°C for 1h; after solution treatment, the test rod was subjected to aging treatment at 1100°C for 5h, and the γ' volume fraction was calculated to be 72% using Image-ProPlus; after a mixed solution of sodium sulfate and sodium chloride (sodium chloride mass concentration of 5%, sodium sulfate mass concentration of 95%) was coated on the surface of the single crystal alloy after aging treatment, the deposition amount of sodium sulfate was 28.5g / m 2 , the deposition amount of sodium chloride is 1.5g / m 2 After a hot corrosion test at 900℃ for 100h, the oxygen weight gain per unit area was 75mg / cm 2 , its hot corrosion resistance is better than the best alloy among the model alloys④.

[0081] In summary, it can be explained that the organizational structure characteristics and thermal corrosion resistance of polycrystalline alloys can be mapped to single crystal alloys, so that the elemental composition of single crystal alloys can be designed according to the test results of polycrystalline alloys, which greatly shortens the time and economic cost of single crystal alloys.

[0082] The method of the present invention can save more than 50% of the time cost in designing single crystal alloys. Specifically, the design cycle of a new type of single crystal high-temperature alloy is divided into a series of processes such as alloy component design, smelting master alloy, refining single crystal, testing key performance, feedback component optimization, etc., and it takes at least 22 months to determine the performance of the new alloy after one iteration. However, using the method of the present invention, it only takes 5 months to complete the mapping of key material science information of single crystals in the polycrystalline state, 2 months to prepare single crystals, and 2 months to test key performance to complete the research and development. The alloy design of the present invention is fast and efficient.

[0083] The method of the present invention can save more than 80% of the economic cost in designing single crystal alloys. In the single crystal method, more than 64 single crystal rods are needed in the exploration stage, each of which costs about 10,000 yuan, and at least 640,000 yuan without counting the test cost. Using the method of the present invention, about 20 ingots are needed in the exploration stage, each of which costs about 1,500 yuan, and about 30,000 yuan without counting the test cost. Taking into account the test and labor costs, the comprehensive economic cost is reduced by 80%.

[0084] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for designing the element composition of a single crystal nickel-based high-temperature alloy, comprising the following steps: The alloy raw materials are melted and cast according to the ratio of nickel-based high-temperature alloy elements to obtain polycrystalline nickel-based high-temperature alloy ingots with different element component contents; The polycrystalline nickel-based high-temperature alloy ingot is subjected to solution treatment and aging treatment in sequence, and the volume fraction of γ' in the polycrystalline nickel-based high-temperature alloy after aging treatment is obtained by detection and calculation; the temperature of the solution treatment is 1250-1350°C, and the holding time of the solution treatment is 2-12h; the temperature of the aging treatment is 1000-1200°C, and the holding time of the aging treatment is 4.5-5.5h; the calculation is performed using Image-Pro Plus; Performing a performance test on the polycrystalline nickel-based high-temperature alloy after aging treatment; the performance test includes a salt-coated hot corrosion test or an anti-oxidation test; The element composition of the single crystal nickel-based superalloy is determined according to the element composition in the polycrystalline nickel-based superalloy ingot, the volume fraction of γ' in the polycrystalline nickel-based superalloy after aging treatment and the performance test results.

2. The method according to claim 1, characterized in that: The conditions of the salt-coated hot corrosion test include: a temperature of 850-950° C. and a time of 50-200 h.

3. The method according to claim 1 or 2, characterized in that: The corrosion solution for the salt-coated hot corrosion test includes a sodium sulfate solution and / or a sodium chloride solution.

4. The method according to claim 1, characterized in that: The polycrystalline nickel-based high-temperature alloy ingot comprises the following elements in percentage by weight: Al 2.0~9.0wt.%; Co 0~11.0wt.%; Cr 2.0~18.0wt.%; W 2.0~13.0wt.%; Mo 0~5.0wt.%; Ta 0~8.0wt.%; Ti 0~8.0wt.%; Ni 60.0~80.0wt.%.

5. The method according to claim 1 or 4, characterized in that: The smelting temperature is 1400-1600°C.

Citation Information

Patent Citations

  • Non-rhenium No.2 generating nickel-base mono high temp alloy

    CN101089214A

  • Chemical milling method used for aeroengine corrosion-resistant single crystal blades

    CN103602985A

  • Environment-friendly chemical milling solution for single crystal high temperature alloy precision casting and chemical milling method

    CN108374173A

  • Nickel based single crystal superalloy modified in oxidation resistance and its production

    JP1993271831A

  • Highly corrosion resistant nickel-base single crystal superalloy and its production

    JP1995300639A